Dekonstruksi Informasi Berita Opini “Perjuangan Berat Menjaga Bahasa Jawa - Kasmanah; Zuriyati; Ifan Iskandar (CBJIS: Cross-Border Journal of Islamic Studies, 2021)
The purpose of this study is to reveal the online news discourse contained in the "Kedaulatan Rakyat" newspaper entitled "Perjuangan Berat Menjaga Bahasa Jawa", which was published on November 30, 2023 and is on page 11. In this discourse, the researcher wants to deconstruct opinion news information in the realm of news structure, the purpose of using language in the article, and the style of language used by the author named Sarworo Soeprapto. The method used is the textual analysis method combined with the concept of deconstruction. While the qualitative method is a research procedure that produces descriptive data. The results of the study illustrate that the first structure in the form of an introduction is presented with a unique paragraph and attracts the attention of readers, namely in the form of a quote from a Javanese campursari song that is currently a hit, namely a song entitled "Nemen". The presentation of a brief background or context regarding the topic to be discussed and describing the issues or problems that are the focus of the opinion is presented appropriately. The second structure, the content section, reviews the author's opinions and views on the issues discussed with precise and clear explanations accompanied by the author's opinions and facts in the field. The third structure in the form of a conclusion, the author concludes and recapitulates the arguments explained and strengthens his opinion statement. The purpose of the article is to express the subjective opinion of the author, build awareness and understanding, and encourage change and action. In addition, the style of language also plays a role in this article. The use of good and easy-to-understand grammar but there is also an idiomatic style of language in the word 'macan ompong' which means someone who looks fierce and scary but actually can't do anything or more simply a ruler without power, something that looks strong but is actually weak. Practitioners of Javanese language stakeholders who have a strong role as motivators and language improvers are unable to show real action in the field on the grounds of weak funds and human resources.